The trouble with Texas cowboys - Brown, Carolyn, 1948- (Brown, Carolyn, 1948- Burnt Boot, Texas series., 2015)
"Can a girl ever have too many cowboys? No sooner does pint-sized spitfire Jill Cleary set foot on Fiddle Creek Ranch than she finds herself in the middle of a hundred-year-old feud. Quaid Brennan and Tyrell Gallagher are both tall, handsome, and rich...and both are courting Jill to within an inch of her life. She's doing her best to give these feuding ranchers equal time--too bad it's dark-eyed Sawyer O'Donnell who makes her blood boil and her hormones hum" --